Tortoise trouble - Joan, Lingard (Great Britain Catnip Books, 2013)
When Robbie moves from the country to the city, he thinks he will never settle into his new school. But when a class project means he gets to talk about his pet tortoise, Herman, Robbie starts to make new friends. But that s when the trouble really starts.